Assessing the selective impact of histone modifying drugs on adenoid cystic carcinoma cells and their stem cell counterparts - Carolina Emerick; Luan César Silva; Yeejin Jang; Pablo A. Vargas; Cristiane H. Squarize; Rogerio M. Castilho (BMC Cancer)
Abstract Background Adenoid cystic carcinoma (ACC) is a rare, malignant neoplasm of the salivary glands that, despite its slow growth, exhibits aggressive behavior, including perineural invasion, high recurrence rates, and distant metastasis. The lack of effective systemic therapies, combined with the resistance of cancer stem cells (CSCs) to standard treatments, highlights the urgent need for novel therapeutic strategies. Methods In this study, we employed a high-throughput screening approach to evaluate a library of 157 histone modification drugs (HMDs) using the UM-HACC-2 A cell line. Two complementary in vitro models were used: traditional two-dimensional culture representing the bulk non‑CSC tumor population and three‑dimensional tumorspheres that enrich for CSCs. Automated liquid handling, high‑content imaging (ImageXpress), and image analysis (MetaXpress) enabled precise quantification of cell viability and tumorsphere characteristics following treatment with HMDs. Results Screening identified 14 candidate compounds that induced statistically significant cell death in non‑CSCs and 11 compounds that were effective against tumorspheres. Key epigenetic targets included histone deacetylases, histone methyltransferases, EZH2, c‑RET, and EGFR. Notably, ITF2357 (Givinostat) induced 84% cell death in non-CSC populations (p < 0.0001), while the histone methyltransferase inhibitors, UNC0631 and LLY-507, elicited cell death rates of 82.5% (p < 0.0001) and 82.3% (p < 0.0001), respectively. In the CSC model, GSK343, an EZH2 inhibitor, induced 35.2% cell death (p < 0.0001). Furthermore, combination assays, pairing HMD hits from CSC and non‑CSC screenings, revealed synergistic effects that significantly enhanced tumor cell death compared to monotherapy. Conclusion These findings demonstrate that CSCs and non‑CSCs respond differently to epigenetic modulation, suggesting that personalized combination therapies targeting both subpopulations may be necessary to improve treatment outcomes for ACC. Although these targeted therapies are still in the early stages of investigation, our study provides a promising pre-clinical foundation for the development of effective, personalized therapeutic strategies for this challenging malignancy.